SOCIAL CONFLICT MANAGEMENT AMONGST COMMUNITY AND COMPANY IN THE PALM OIL PLANTATION LOCATION KINANDE VILLAGE, LEMBAH BAWANG, BENGKAYANG - A.B.Tangdililing Tangdililing (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
Social conflicts that occured and are not managed can have an impact on low productivity community and related parties, because the climate of the social environment is not conducive. Conversely, if the potential for social conflict can be managed properly could a positive impact on efforts realizing social welfare, but if it is unable to manage it, it can have a negative impact on the peace, unharmony social life. This paper focuses on aspects of social problems which cold be the potential to emerge, namely the potential for conflict and the problem of economic access gaps among local communities and migrants, smallholders and companies, and between communities and large plantations. This type of research is classified as descriptive research with a qualitative approach that is to describe the situation and conditions and the existence of oil palm plantation companies in Kinande Village, Lembah Bawang District, Bengkayang district. The results obtained that the conflict between the two parties was managed in a way such as holding negotiations to reach a win-win solution agreement, such as forming a plasma farmer, and allowing the company to use the land on the agreement among Kinande people andpalm oil plantation company.